Analisis SWOT Sebagai Upaya Meningkatkan Volume Usaha Jajanan Ros Kabupaten Bengkayang - Rosalia Rosalia; Sabinus Beni; Benedhikta Kikky Vuspitasari; Veneranda Rini Hapsari (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
The purpose of this study is to analyze Efforts to Increase JR Business Volume through SWOT Analysis. The method used in this study is a qualitative research method. The subjects in this study amounted to 8 respondents using in-depth interview techniques. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results of this study show that there are several aspects that affect the strength, namely: good product taste, many flavor variants, easy-to-reach business location, affordable product prices, good service. Meanwhile, the disadvantages are as follows: JR snack products cannot be stored for too long, the product packaging is still standard, the production process is still carried out manually, and the supply of stock is not much. For the opportunity itself, namely providing a new product menu, developing products that are in demand by many consumers. And for the threat as follows: the increasing level of competitors, competitors with the same type of products